(untitled) (Malaysian Journal of Civil Engineering, 2018)
Natural Draught Cooling Tower (NDCT) is an important and essential structure in nuclear and thermal power stations as it contributes both to the energy efficient output and balance to an environment. From the structural point of view, high rise concrete structure is subject to various dynamic loads in an unfavorable way. Wind loading is important in NDCT design for structural safety, elastic stability, vibration properties and the initiation of concrete cracking in comparison to other structures. The behavior change of NDCT due to the variation of shell thickness when NDCT rested on a vertical pile foundation is very interesting. Therefore, the objective of the present paper is to briefly present the finite element modeling and analytical study of NDCT with twenty-seven different types of shell thickness models for the same height of NDCT. Each model is identified based on the separate case number from 1 to 27, and FEM analysis was carried out using Staad Pro-V8i software considering gravity loads, wind load. Further, design wind pressure at different levels along the height of NDCT was calculated as per IS 875 (part 3) 1987 code after applying Interference factor (IF) of 1.573. Due to the lack of wind study findings, the IF was considered as 1.573 while the maximum value of IF was 1.43 as per BS: 4485 (1975). Distribution of wind pressure at each level of NDCT in the circumferential direction was as per IS11504-1985. The overall study identified optimum shell thickness varying models to obtain the optimum foundation as well as super-stable structure. Further, the comparison was made between the guest and peak factor method and found that wind load due to gust factor method was critical and therefore recommended.